Lymphatic cysts after gynecological cancer surgery: risk factors, diagnosis and treatment - Т. Т. Rogovskaya; I. V. Berlev (Опухоли женской репродуктивной системы)
Lymphatic cysts, also known as lymphocele, are one of the most common complications after pelvic and paraaortic lymph node dissection in patients with gynecological cancers. Despite the high incidence of this complication, no specific guidelines on the diagnosis and treatment of lymphocele have been developed so far. This article analyzes the incidence of lymphatic cysts, risk factors, and currently available options for their diagnosis and treatment.